Arthur Koestler’s Dichotomy – The Yogi and the Comissar – in Danilo Kiš’s Literary Reflections - Utasi, Csilla (Anafora, 2024)
In Danilo Kiš’s essays and interviews, references to Arthur Koestler’s works multiply after 1978. In his reflections, Kiš not only evokes the trustworthy witness of the twentieth century, but also characterises his own novels and short stories with Koestler’s dichotomy, the contrast between the yogi and the commissar. In his 1942 essay, Koestler contrasts two irreconcilable social attitudes: the yogi, who is observant of existence and aims to maintain his relationship to it, and the commissar, who prioritises social action and wants to change the world. Koestler traced his intellectual trajectory from the position of the commissar to that of the yogi in his two-volume autobiography (Arrow in the Blue, The Invisible Writing). While in prison in Seville, he came to experience the ‘oceanic feeling’ associated with being a yogi. Kiš considered the “metaphysical” experience an inalienable element of the literary work. However, the two authors interpreted the experience of being in very different ways. Koestler gives a scientific-philosophical explanation of the ‘oceanic feeling’. Meanwhile, Kiš’s position can be illuminated by Paul Ricoeur’s study The Hermeneutics of Revelation. According to the author of this work, Kiš shares Ricoeur’s view that the literary work gives one the elementary experience of belonging to the world, but also assigns the task of bearing witness to the horrors of twentieth-century history to poetic discourse.